Why do young children die in the UK?: a comparison with Sweden - Tambe, Parag; Sammons, Helen M.; Choonara, Imti (BMJ, 2015)
Background The UK has a high child mortality rate, whereas Sweden’s is lower (under-five mortality rates of five and three, respectively, in 2011).We therefore wished to compare causes of death in young children aged <5 years in the two countries. Methods Under-five mortality data were obtained from the Office of National Statistics for each of the individual countries within the UK for 3 years (2006–2008). Data for Sweden for the same period were obtained from the National Board of Health and Welfare. Causes of death were compared statistically using χ2 test. Results There were a total of 14 104 and 1036 deaths aged <5 years in the UK and Sweden, respectively, between 2006 and 2008. The total numbers of live births during the same period were 2 295 964 and 315 884, respectively. The overall mortality rate in the UK was 614 per 100 000 children which was significantly higher than that in Sweden (328; p<0.001). The mortality rates for the three main causes of death in the UK ( prematurity, congenital malformations and infections) were 138.5, 112.1 and 63.9, respectively, per 100 000 children. The mortality rates for the same three conditions in Sweden were 10.1, 88.6 and 34.8, respectively. They were all significantly more frequent in the UK than in Sweden (p<0.001), as were the majority of the disorders. Treatable infections, such as pneumonia, meningitis and septicaemia, in both neonates and young children had significantly higher mortality rates in the UK than in Sweden ( p<0.001). Conclusions In order to reduce the mortality rate in the UK, we need to try and reduce the causes of prematurity. Additionally, the care of children with treatable infections should be reviewed to understand ways in which to reduce the differences in mortality seen.